On the phonemicization of the Old High German i-umlauts (Atti del Sodalizio Glottologico Milanese, 2024)
In this article it will be argued that the Old High German i-umlaut phenomena produced phonemic changes before the factors that triggered them off changed or disappeared. When they reached their final stages, the products of i-umlaut became distinctive in the phonological system of the language and contrastive at a lexical level.